Pengaruh E-book Fashion Product Portfolio Terhadap Motivasi Belajar Mahasiswa - Andriani, Siska; Arrsyi, Esty Nurbaity; Sesnawati, Yeni (Practice of Fashion and Textile Education Journal, 2024)
This study aims to see how the influence of e-book Fashion Product Portfolio on students’ learning motivation. This research is a quantitative approach with an experiment method, pre-experimental design with intact group comparison type. The population in this research are Design Mode’s student that currently took Portfolio subject on 2023/2024 school period with total 43 students. The data collection technique was carried out using a questioner. The validation test used is construct validity test. The analysis technique used is the chi square test. The theory used is the theory of learning motivation by Frederick J. McDonald. The result shows on this study that there is influence on e-book Fashion Product Portfolio on students’ motivation learning. This is caused by e-book Fashion Product Portfolio is an electric book containing a systematic portfolio format regarding the creation of fashion products from design concept to product realization that can be used anywhere and at any time using electronic devices, making it easier for students to do assignments and study independently. This advantage is proven to increase learning motivation, especially in the aspect of the indicator “lebih senang mengerjakan tugas secara mandiri” which obtained the highest percentage. Keywords : learning motivation, e-book, portfolio